Effects of a High Fat Diet and of Intravenous Infusions of Cholesterol on Arterial Pressure in Rabbits - Burstyn, P. G. (1972)
In 8 rabbits arterial pressure was measured by the ear capsule method. After a 2-week control period, the fat content of the diet was approximately tripled. Arterial pressure in the animals began to rise within 10 days and after 4 weeks was about 40% above control. There were no significant changes in plasma cholesterol levels. Thirty-three rabbits were investigated in acute experiments. Fourteen were infused with an emulsified cholesterol preparation at the rate of 0·3 mg/kg/hour. This caused a rapid rise in pressure with a mean increase of over 40% above control at the end of 4 hours. An emulsion of talc was infused into 8 rabbits: there was no change in arterial pressure at the end of 4 hours. Dialysed rabbit plasma containing cholesterol was infused into 11 animals at the rate of 0·3 mg cholesterol/kg/hour: this caused a pressure rise of 17% after 4 hours. The experiments suggest that the physicochemical state of cholesterol in the plasma may be much more important than its total concentration.